THE IMPORTANCE OF COMPLIMENTS IN THE BRITISH AND RUSSIAN CULTURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article discussed the different cultural notions of British and Russian attitude towards compliments, there was a discussion on the topic of how people from two particular ethnic groups react to the giving and receiving compliments.